Pemutusan Hubungan dalam Perkawinan : Studi Fenomenologi Pada Wali Anak Korban Pengasuhan Bermasalah - Andys Tiara; Rita Pranawati (Prisani Cendekia Institute, 2022)
Abstract: Marriage is part of the social system. Marriage is the basis for forming a family, but the life or marriage is not as easy as imagined. Unresolved and not immediately anticipated of redifinisi and deterioration will certainly lead to the termination of the relationship in marriage which has an impact on indifference to the situation and circumstances of the family at home, especially child care, causing problematic parenting. This study aims to understand and identify the things that causes dissolution in marriage that makes children to experience parenting problems or conflicts in their families. Through the phenomenological method, qualitative approach and symbolic interaction theory, the results of the study found various conflicts behind the termination of a relationship in a marriage so that children become victims of problematic parenting, namely infidelity or affair, Domestic Violence (KDRT), Economy and Selfishness. The things that make a marriage (family) to be vulnerable in dealing with until resolving and overcoming conflicts are influenced by commitment, family conflicts, motivation to build marital relationships and mental readiness. The results of this study are expected to provide input or thoughts on solving problems related to the termination of marital relations so as to provide social understanding in the form of awareness for the community in building a family life.